2021
DOI: 10.3390/app11199046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Changes in Spectral Signal According to Gas Flow Rate in Laser-Induced Breakdown Spectroscopy

Abstract: In a laser-induced breakdown spectroscopy (LIBS) system that performs elemental analysis of a target by acquiring the emission of plasma generated on the material surface by a focused laser, the plasma signal may be affected by the flow of the surrounding gas. A flow of gas may be present when LIBS measurements are performed in a special environment where an inert gas is normally applied. In such an environment, the flow of gas may affect the intensity of emission generated in plasma. The LIBS spectral intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The influence of ambient pressure on laser-induced plasma has been studied extensively. 15–19 Researchers found that ambient pressure can significantly affect the plasma morphology, 15,16 spectra, 18,19 electron temperature, electron density, 20 etc. , but there are few studies on the influence of ambient pressure on the LTE of LIP.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of ambient pressure on laser-induced plasma has been studied extensively. 15–19 Researchers found that ambient pressure can significantly affect the plasma morphology, 15,16 spectra, 18,19 electron temperature, electron density, 20 etc. , but there are few studies on the influence of ambient pressure on the LTE of LIP.…”
Section: Introductionmentioning
confidence: 99%